THE EFFECTIVENESS OF PROMOTING HYDROPONIC VEGETABLES AND PRODUCTS THROUGH INSTAGRAM WITH BRAND AWARENESS AS A MODERATING VARIABLE AT PT. KEBUN SAYUR - Rahmawati, Alya Firda; Nurhadi, Eko; Setyadi, Taufik (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
PT. Kebunsayur Surabaya promotes hydroponic vegetables and processed products on Instagram but has yet to achieve widespread reach. Popular posts based on monthly reports only get 29 likes; this figure is relatively low for a business account. This research aims to analyze the effectiveness of social media Instagram @kebunsayursurabaya using the EPIC Model and analyze the influence of promotional effectiveness on the volume of consumer purchases of vegetables and hydroponic preparations moderated by brand awareness. The research method used is Structural Equation Modeling (SEM) based on Partial Least Square (PLS), especially with the WarpPLS 8.0 program. Primary data was collected through a questionnaire with a sample of 55 respondents taken using techniques non-probability sampling, namely purposive sampling. The research results show that the promotion of Kebunsayur Surabaya via Instagram is very effective, with a value of 4.39. The effectiveness of the promotion has a positive and significant effect on purchase volume with a path coefficient value of 0,454 and brand awareness moderates the effectiveness of promotion on purchase volume positively and significantly with a path coefficient value of 0,223